Eco-Leadership: Peran Pemimpin dalam Mewujudkan Ekonomi Berkelanjutan dan Ramah Lingkungan - Aria Eka Agustina Abdullah; Nila Malikhah; Savina Nur Lailiyah; Mochammad Isa Anshori (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
This article examines the crucial role of eco-leadership in achieving a sustainable and environmentally friendly economy, particularly within the dynamic context of the digital age and industry 4.0. In this era, the pressure on companies to integrate environmentally friendly initiatives into their corporate social responsibility (CSR) programs is increasing, supported by government policies and regulations in Indonesia. This article highlights that the effectiveness of environmental protection and sustainable corporate performance can be measured through various practices such as waste management, pollution control systems, recycling, and environmental impact mitigation. In conclusion, environmentally oriented leadership plays a central role in promoting more responsible business practices and behaviors, which are essential for reaching sustainability targets and realizing an economy that is not only financially profitable but also responsible for environmental preservation.1